2001
DOI: 10.1161/hs1101.098520
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Effects on Atherogenesis and Scavenger Enzymes of Intracranial and Extracranial Arteries in Men Without Classic Risk Factors for Atherosclerosis Editorial Comment

Abstract: Background and Purpose-Atherosclerosis occurs later and is less extensive in intracranial arteries than in extracranial arteries. However, the mechanisms responsible are poorly understood. A previous study has suggested a better antioxidant protection of intracranial arteries. Methods-To assess the influence of age on arterial activity of antioxidant enzymes and atherogenesis, we compared intracranial and extracranial arteries of humans of different ages who retrospectively lacked confounding classic risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 35 publications
3
101
0
2
Order By: Relevance
“…This antioxidant activity decreases with age, coinciding with a rapid acceleration of atherosclerosis in intracranial arteries. 9 A previous work also showed that adiponectin levels were lower in symptomatic ICAD when compared with other stroke subtypes. Adiponectin is an antiatherogenic protein that improves insulin sensitivity.…”
Section: Discussionmentioning
confidence: 88%
“…This antioxidant activity decreases with age, coinciding with a rapid acceleration of atherosclerosis in intracranial arteries. 9 A previous work also showed that adiponectin levels were lower in symptomatic ICAD when compared with other stroke subtypes. Adiponectin is an antiatherogenic protein that improves insulin sensitivity.…”
Section: Discussionmentioning
confidence: 88%
“…The molecular mechanisms responsible for the increased mitochondrial oxidative stress in the aged vascular system are multifaceted and likely involve pathways similar to those contributing to enhanced mitochondrial ROS production in the old heart. These mechanisms encompass ETC dysfunction (196), activa- tion of NOX4 (NADPH oxidase 4, located in the mitochondrial membrane) (1), declines in glutathione content (28), and impairments in antioxidant defenses (34,193,201). In addition, an age-related dysregulation of NF-E2-related factor 2 (Nrf2)-mediated antioxidant response is likely to contribute to mitochondrial oxidative stress in the vascular system (191,192,195).…”
Section: Mechanisms Of Mitochondrial Dysfunction and Altered Mitochonmentioning
confidence: 99%
“…Results were expressed as femtograms of HT1080 RNA per microgram of total RNA. Primers used were as follows: TIMP1 sense, 5Ј-TCTGGCATCTGGCATCCTC-3Ј; TIMP1 antisense, 5Ј-AGCAAAGTGACGGCTGCTCTGG-3Ј; TIMP2 sense, 5Ј-GCGGTCAGTGAGAAGGAAGTGG-3Ј; and TIMP2 antisense, 5Ј-CTTGCACTCGCA-GCCCATCTG-3Ј (54,55).…”
Section: Neuroprotective Treatment With Autologous Bmcs and Transgenementioning
confidence: 99%